Ömer Seyfettin'in diyet, And, Teke tek, Kurbağa Duası, Keramet, Yüksek Ökçeler, Topuz hikayelerindeki birleşik fiil ve deyimlerin Özbekçe muadilleriyle karşılaştırma - Khamidova, Zamirakhon (My University, 2009)
This study examines seven short stories (“Ant”, “Diyet”, “Keramet, “Kurbağa Duası”, “Teke Tek”, “Topuz”, “Yüksek Ökçeler”) by Ömer Seyfettin from the point of view of compound verbs and idioms which then are compared with their Uzbek counterparts. These seven stories are translated into Uzbek. An index of the lexic content of the stories is given together with the meaning of the words in Uzbek. The compound verbs and idioms which occur in the stories is listed. These compound verbs and idioms are classifed according to a number of criteria and compared with their Uzbek counterparts. The terminology, definition and classification of compound verbs and idioms – according to grammarians of Turkish – is analysed.
Keywords: Türk Dili